Problems of Medical Problems of Medical Emergency Law from the Perspective of Abortion Crimes (Government Regulation Number 28 of 2024): Abortion Crimes - Leksono, Totok Minto; Yusuf Albar, Mohammad Haris; Bramantyo, Rizki Yudha (Journal of Law, Politic and Humanities, 2025)
Abortion is a highly controversial issue in Indonesia, sparking debates on legal, ethical and moral aspects. In the context of regulatory developments, Government Regulation (PP) No. 28 of 2024, which is the implementation of Law No. 17 of 2023 concerning Health, provides space for abortion in medical emergencies. Medical abortion, also known asMedically Induced Abortion, performed to save the mother's life or prevent serious malformations in the fetus. Criminal Induced Abortionmeans abortion carried out without a valid medical reason and can be subject to legal sanctions. The purpose of this study is to analyze the regulation of abortion in medical emergencies according to PP No. 28 of 2024, identify legal problems that arise during implementation and provide recommendations to improve the effectiveness of the implementation of the regulation. This study uses normative legal research methods to analyze the provisions on abortion contained in the articles of the Regulation. The findings show that this regulation has a major impact on regulating abortion practices, but challenges remain, including unclear regulations and potential violations of patient rights. Therefore, corrective actions are needed to ensure fair, transparent, and efficient implementation of the regulation and to guarantee the protection of women's health rights.